Neoadjuvant Chemotherapy Followed by Radical Surgery versus Concurrent Chemo-Radiotherapy in the Treatment of Locally Advanced Cervical Cancer: A Multicenter Retrospective Analysis. Issue 2 (1st February 2022) - Sala, Paolo; Bogliolo, Stefano; Barra, Fabio; Fazio, Alessandra; Maramai, Mattia; Cassani, Chiara; Gardella, Barbara; Babilonti, Luciana; Giannelli, Flavio; Mammoliti, Serafina; Spinillo, Arsenio; Ferrero, Simone; et al.
Abstract: Objectives: This study aims to evaluate oncological outcomes in women affected by locally advanced cervical cancer (LACC) treated by neoadjuvant chemotherapy before radical surgery (NACT + RS) or concurrent chemo-radiotherapy (CCRT). Methods: This was a multicenter retrospective analysis of data related to women with LACC (FIGO stage IB2-IVA), who were treated by NACT + RS or CCRT between November 2006 and January 2018. The first endpoints were the evaluation of disease-free survival (DFS) and overall survival (OS); univariate and multivariate analyses were performed for identifying the prognostic factors independently associated with these oncological outcomes. Results: Overall, 106 women were included in the analysis; 55 of them (51.9%) underwent NACT + RS and 51 (48.1%) CCRT, respectively. Patients in the NACT + RS group had a significant better five-year DFS and five-year OS than those in the CCRT group (77.4% vs. 33.4%, p  < .001 and 93.8% vs. 56.5%, p  = .003). In the multivariate analyses, treatment choice (NACT + RS or CCRT) was the only independent prognostic factor for predicting both DFS (HR = 3.954; 95 CI = 1.898–8.236; p  < 0.001) and OS (HR = 5.330; 95 CI = 1.563–18.178; p  = 0.008). Conclusions: This retrospective study demonstrated an improved survival outcome for patients undergoing NACT + RS compared with those undergoing CCRT. Our findings seem to support the use of NACT before RS as an effective alternative option to CCRT standard therapy.